Systemic theory, strong institutionalism and representative politics: another way to a radical democratic politics - Danner, Leno Francisco (DoisPontos, 2016)
Starting from the critic against two theoretical-political points of the Jürgen Habermas’ theory of modernity, i.e. his understanding of the Western modernization as systemic institutional self-differentiation, self-referentiality and self-subsistence, and his conception of a juridical-political procedural paradigm based on such notion of modernization, I argue that the systemic theory concerning modernization leads to strong institutionalism and to depoliticization of the institutional structuration, legitimation and evolution. The basic characteristic of systemic theory, which is the institutional self-referentiality and self-subsistence regarding political praxis and social normativity, autonomizes social systems of justifying and organizing themselves according to an inclusive democratic political praxis and to a biding notion of social normativity, depoliticizing them. From here emerges a radical separation between systemic institutional dynamic and democratic political-normative praxis, between institutions and civil society, in that systemic institutions become independent and closed in relation to politics and social normativity, allowing only a representative political role to social movements and citizen initiatives, centralizing and monopolizing the institutional legitimation and the social evolution inside the very own institutions. A radical democratic political praxis which can face such strong institutionalism based on the systemic theory must politicize both the liberal’s notion of Western modernization and its consequent strong institutionalism, refusing the systemic theory as epistemological-political basis to the foundation of the contemporary institutional constitution and legitimation. It signifies also the normative-political centrality of the civil society’s arena, practices and social subjects as the platform to institutional grounding and evolution.